2021
DOI: 10.1159/000518809
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous Noise on Optical Coherence Tomography as an Early Finding of Brolucizumab-Related Intraocular Inflammation

Abstract: We describe a case of brolucizumab-related intraocular inflammation (IOI) detected using vitreous haze on optical coherence tomography (OCT) at an early stage before the patient was aware of any symptom. A 69-year-old female presented with decreased right vision. The patient was diagnosed with pachychoroidal neovasculopathy and started intravitreal aflibercept (IVA) with a 3+ treat-and-extend strategy (TAE). Although the serous retinal detachment (SRD) disappeared after IVA treatment, the patient was managed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In a sub-analysis focusing on Japanese PCV patients within the HAWK and HARRIER studies, the incidence of intraocular inflammation was reported in 15.4% [38]. Furthermore, the incidence of intraocular inflammation in Japanese patients ranges from 9.4% to 28.6% in clinical studies [23][24][25][26][27][28][29][30][31]. Thus, brolucizumab-related intraocular inflammation is a significant concern for the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sub-analysis focusing on Japanese PCV patients within the HAWK and HARRIER studies, the incidence of intraocular inflammation was reported in 15.4% [38]. Furthermore, the incidence of intraocular inflammation in Japanese patients ranges from 9.4% to 28.6% in clinical studies [23][24][25][26][27][28][29][30][31]. Thus, brolucizumab-related intraocular inflammation is a significant concern for the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…The heightened risk includes the potential occurrence of occlusive retinal vasculitis occurrence, which can lead to irreversible visual impairment [22]. Although brolucizumab is expected to be an effective therapeutic agent for PCV treatment, intraocular inflammation management, which frequently occurs in the Japanese population [23][24][25][26][27][28][29][30][31], is a major challenge. In clinical practice, measures are being taken to prevent the onset of intraocular inflammation by the concomitant use of sub-tenon's capsule triamcinolone acetonide injection (STTA) [23,30].…”
Section: Introductionmentioning
confidence: 99%
“…Other reported adverse effects include lenticular opacities, punctate keratitis, corneal abrasion, posterior capsule opacification, cataracts, increased intraocular pressure, blepharitis, conjunctivitis, and iritis [ 9 ]. Meanwhile, Yoshikawa et al [ 10 ] reported a case of brolucizumab-associated inflammation in the vitreous cavity, manifesting as a black smoke-like shadow on optical coherence tomography (OCT) examination. In our retinal clinic, we encountered several cases of vitreous opacity (VO) after intravitreal brolucizumab injection, with an appearance similar to that of asteroid hyalosis (AH).…”
mentioning
confidence: 99%